Adaptation and validation of the Brazilian version of the Measure of Moral Distress for Healthcare Professionals (MMD-HP BR) in the context of palliative care - Julianna Rodrigues Beltrão; Marianna Rodrigues Beltrão; Rafaella Stradiotto Bernardelli; Renato Soleiman Franco; Elizabeth G. Epstein; Carla Corradi-Perini (BMC Palliative Care, 2023)
Abstract Background The Measure of Moral Distress for Health Care Professionals (MMD-HP) scale corresponds to the update of the globally recognized Moral Distress Scale–Revised (MDS-R). Its purpose is to measure moral distress, which is a type of suffering caused in a professional prevented from acting according to one’s moral convictions due to external or internal barriers. Thus, this study has the objective to translate, culturally adapt, and validate the Brazilian version of the MMD-HP BR in the context of Palliative Care (PC). Methods The study had the following steps: translation, cross-cultural adaptation and validation. The MMD-HP BR is composed of 27 Likert-rated items for frequency and intensity of moral distress. In total, 332 health professionals who work in PC participated in the study, 10 in the pre-test stage, and 322 in the validation stage. Results It was possible to identify six factors, which together explain 64.75% of the model variation. The reliability of Cronbach’s alpha was 0.942. In addition, the score was higher in those who are considering or have already left their positions due to moral distress, compared to those who do not or have never had such an intention. Conclusions MMD-HP BR is a reliable and valid instrument to assess moral distress in the PC context. It is suggested that the scale be standardized in other healthcare contexts, such as clinical settings. In addition, further research on moral distress is encouraged to identify and reduce the phenomenon and its consequences.